The Covalent Capture of [2]Catenanes Using Self-Templating Allyl Amide-Appended 2,6-bis(triazol-4-yl)pyridines - Manning, Patrick (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
This thesis, entitled "The Covalent Capture of [2]Catenanes Using Self-Templating Allyl Amide-Appended 2,6-bis(triazol-4-yl)pyridines" describes the synthesis of self-templating [2]catenanes using the N-allyl-4-methylenebenzamide-appended 2,6-bis(triazol-4-yl) pyridine (btp) molecular scaffold. This thesis is divided into eight chapters which are summarised below. Chapter one introduces both historic and current methodologies employed in the synthesis of mechanically interlocked molecules (MIMs). This will primarily focus on the self-templating methodology, outlining its advantages and disadvantages in MIM synthesis. The 1,4-disubstitued 1,2,3-triazole and its supramolecular interactions will then be briefly discussed. This will have an emphasis on its incorporation into the btp motif. Following this, the host-guest chemistry of mechanically interlocked anion receptors will be explored. Finally, the previous works from the Gunnlaugsson research group relevant to this thesis will be introduced. This which have a particular focus on the N-allyl-4-methylenebenzamide-appended btp molecular scaffold and its reported incorporation into self-templated [2]catenanes. Chapter 2 details the synthesis of a small library of N-allyl-4-methylenebenzamide-appended btp molecules, derivatised at the 4-pyridlyl position of the btp motif. These catenane precursors will form the basis of this thesis. In addition to this, the development of a one-pot methodology towards these compounds will be discussed. Chapter 3 will explore the employment of this library of N-allyl-4-methylenebenzamide-appended btp derivatives in the covalent capture of self-templated [2]catenanes. The effects of 4-pyridyl functionality on the self-templating characteristics of the molecular scaffold will be elucidated. Both the solid-state and solution characteristics of the resulting [2]catenanes will be compared and contrasted respectively. Several catenanes will also be synthesised via functional group interconversion. Chapter 4 will detail the covalent capture of btp [2]catenanes at high concentrations. The results of which will be used to elucidate the self-templating characteristics of the N-allyl-4-methylenebenzamide-appended btp molecular scaffold. Chapter 5 will briefly explore the anion binding properties of btp [2]catenanes. This will investigate host-guest binding modes. The development of triazolium derivatives of the btp catenane will then be detailed, this will be followed by a comparative exploration of its anion-binding properties. Chapter 6 will present the conclusions of work carried out in this thesis, and Chapter 7 details the experimental procedures employed though out the thesis. A list of literature references will then be provided, followed by the Appendix, which contains supplementary information.
APPROVED
Keywords: Supramolecular Assemblies; Covalent Capture; Catenanes; Mechanical Bond; Molecular Recognition; Mechanically Interlocked Molecules; Nuclear Magnetic Resonance; Self-assembly